Evaluation of particulate matter (PM10) emissions and its chemical characteristics during rotary harrowing operations at different forward speeds and levelling bar heights. (October 2020) - Maffia, Jacopo; Balsari, Paolo; Padoan, Elio; Ajmone-Marsan, Franco; Ricauda Aimonino, Davide; Dinuccio, Elio
Abstract: Particulate matter (PM) is an air pollutant which poses a considerable risk to human health. The agricultural sector is responsible of the 15% of the total anthropogenic emissions of PM10 (PM fraction with aerodynamic diameter below 10 μm) and soil preparation activities have been recognized as one of the main drivers of this contribution. The emission factors (EF) proposed by European environmental agency (EEA) for tilling operations are based on very few studies, none of which has been made in Italy. Moreover, few studies have considered the influence of operative parameters on PM10 emissions during tilling. The aim of this work was to assess PM10 emission and dispersion during rotary harrowing and to understand how operative parameters, such as forward speed and implement choice may affect PM release. A further objective was to assess the near field dispersion of PM10 to address exposure risks. Emission factors (EFs) were determined during two different trials (T1 and T2). During T1, the effect of tractor speeds (0.6, 1.1 and 1.7 m s −1 ) on PM10 emissions was investigated, while in T2 a comparative essay was made to study the influence of levelling bar height on emissions. The average ground level downwind concentrations of PM10 during harrowing operation was estimated through dispersion modelling. The observed PM10 EFs for rotary harrowing were 8.9 ± 2.0 mg m −2 and 9.5 ± 2.5 mg m −2 on T1 and T2, respectively. The heavy metal content of soil-generated PM10 was also assessed. In the generated PM, the elemental concentrations were higher than ones in soil. As, Cd and Ni concentration levels, determined in PM10 near to the tractor path, were also high, being several times higher than the annual average regulatory threshold levels in ambient air, as defined by the European regulation. Graphical abstract: Image 1 Highlights: PM10 emission factors for rotary harrowing have been determined. The effect of three forward tractor speeds on the emissions was assessed. Relevant heavy metal contents were found in emitted PM10 . Future studies should address other common agricultural operations. Abstract : PM10 emission factors for rotary harrowing have been determined with different tractor speeds, and relevant metal contents were found in emitted PM10 .